Simultaneous determination of four ethanol biomarkers in blood: avalidated method for use in forensic toxicology in 257 postmortem samples - Demirel, Göksun; Erol Öztürk, Yeter (Cukurova Medical Journal, 2024)
Purpose: Ethyl alcohol is the most widely and legally available intoxicating substance. However, excessive consumption is associated with numerous negative social consequences, including the potential for significant health risks. Rapid and simple diagnosis of alcohol use is necessary to initiate appropriate and effective treatment and is critical in forensic toxicological analysis. Ethanol biomarkers have clinical utility in the detection, diagnosis, and treatment of alcohol use disorders. Materials and Methods: An analytical method for the simultaneous determination of four different alcohol biomarkers ethyl glucuronide (EtG), ethyl sulphate (EtS), N-acetyltaurine (NAcT), and 16:0/18:1-phosphatidyl ethanol (PEth) in blood samples from forensic cases was developed, validated and verified for the accurate monitoring of alcohol abuse and dependence. Analyses were performed using a liquid chromatography-mass spectrometry system. Results: 257 blood and vitreous samples were collected from 255 male and 2 female subjects aged 16-80 years (average 44±14.82) from the Forensic Medicine Council of Turkey and analyzed for ethanol biomarkers and calculated ethanol concentrations. A total of 257 blood samples were found to contain ethanol, with concentrations ranging from 12.0 to 444.0 mg/dL. Vitreous concentrations ranged from 23 mg/dL to 597 mg/dL. The limit of detection (LOD) for EtG, EtS, NAcT, and PEth were 3.1, 3.9, 7.3, and 5.7 ng/mL respectively in blood samples. The limit of quantification (LOQ) for EtG, EtS, NAcT, and PEth were 7.8, 8.4, 18.3, and 13.1 ng/mL, respectively in blood samples. Conclusion: The method has potential in forensic toxicology as an invaluable tool for the accurate and simultaneous identification of biomarkers of alcohol use and dependence in different biological samples.